Metallic ion-based graphene oxide functionalized silk fibroin-based dressing promotes wound healing via improved bactericidal outcomes and faster re-epithelization. (1st May 2022) - Gupta, Sharda; Prasad, Pushpa; Roy, Amit; Alam, Mohammad Mahtab; Ahmed, Irfan; Bit, Arindam
Abstract: An ideal wound dressing material should enhance the wound healing process and must avoid bacterial contamination. In this study, the synergistic effect of graphene oxide (GO), silver (Ag) and magnesium (Mg) based silk electrospun nanofibrous film on wound healing was evaluated. It reports the influence of essential elements Mg and Ag during the skin regeneration process. Silver and magnesium nanoparticles were doped in graphene oxide. The goal of the present study was to fabricate an electrospun nanofibrous patch with nanoscale fillers to improve the wound recuperation manner and decrease the recuperation time to forestall microorganism infections and improve cellular behavior. Doping was done to insert Ag + and Mg 2+ ions in the crystal lattice of GO to overcome the disadvantage of aggregation of Ag and Mg nanoparticles. In this study, Mg 2+ and Ag + ions doped GO functionalized silk fibroin/PVA dressing material was prepared using the electrospinning technique. It was found that, Mg-GO@NSF/PVA and Ag/Mg-GO@NSF/PVA film possess good cytocompatibility, low hemolytic effect and effective antibacterial and anti-biofilm activities. Furthermore, their improved hydrophilicity and mid-range water vapor transmission rate allow them to be a suitable wound dressing material. Tensile strength of the composite silk film were enhanced relatively to silk/PVA film. The effect of prepared film on wound repair were investigated in excision rat model. It indicates, the wound covered with Ag/Mg-GO@NSF/PVA film showed the highest wound contraction rate and re-epithelization, allowing faster repair of wound sites. In conclusion, the development of metallic ions doped GO based silk fibroin/PVA is a promising approach towards development of antibiotic free wound dressing material. It prevents anti-biofilm formation and also provides adequate therapeutic effects for accelerating wound healing.